2007
DOI: 10.1107/s1600536807025901
|View full text |Cite
|
Sign up to set email alerts
|

Poly[[tetraaqua(μ6-benzene-1,2,4,5-tetracarboxylato)dicobalt(II)] dihydrate]

Abstract: Key indicators: single-crystal X-ray study; T = 298 K; mean (C-C) = 0.004 Å; Hatom completeness 72%; disorder in solvent or counterion; R factor = 0.038; wR factor = 0.103; data-to-parameter ratio = 14.4.The asymmetric unit of the title coordination polymer, {[Co 2 (C 10 H 2 O 8 )(H 2 O) 4 ]Á2H 2 O} n , contains two crystallographically distinct Co II cations, located on inversion centers. Each Co II cation exists in an octahedral coordination environment formed by two water molecules and four carboxylate grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[60][61][62] Structural polymorphism is occasionally encountered in MOFs. [63][64][65][66] In most cases, different condensations of salt are formed when one works at different temperatures in the hydrothermal synthesis. [67][68][69][70] For example, in a neutral or slightly acid medium the hydrogen-bonded network [Co(H 2 O) 6 ](dicarboxylate) is formed at temperatures below 90 1C, and it transforms into the one-dimensional Co(H 2 O) 4 (dicarboxylate) for temperatures between 100 and 120 1C and to a two-dimensional Co(H 2 O) 2 (dicarboxylate) at a slightly higher temperature.…”
Section: Cobaltmentioning
confidence: 99%
“…[60][61][62] Structural polymorphism is occasionally encountered in MOFs. [63][64][65][66] In most cases, different condensations of salt are formed when one works at different temperatures in the hydrothermal synthesis. [67][68][69][70] For example, in a neutral or slightly acid medium the hydrogen-bonded network [Co(H 2 O) 6 ](dicarboxylate) is formed at temperatures below 90 1C, and it transforms into the one-dimensional Co(H 2 O) 4 (dicarboxylate) for temperatures between 100 and 120 1C and to a two-dimensional Co(H 2 O) 2 (dicarboxylate) at a slightly higher temperature.…”
Section: Cobaltmentioning
confidence: 99%
“…For background to the benzene-1,2,4,5-teracarboxylate ligand in coordination polymers, see: Andruh et al (2011); Clarke et al (2012); Jiang et al (2008); Aghabozorg et al (2007); Chu et al (2001); Liu & Ding (2007); Wu et al (2006). For related structures, see: Zhan & Li (2010); Luo et al (2007); Yang et al (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…In recent years, many successful implementation of crystal engineering concepts has produced a great deal of coordination and supramolecular networks (Andruh et al, 2011), many of which exhibit unusual and fascinating architectures (Clarke et al, 2012). The benzene-1,2,4,5-teracarboxylate ligand as a multi-connecting ligand is also an excellent candidate for the structuring of coordination networks (Jiang et al, 2008), and comparatively few examples have been reported in relation to applying it to the building of coordination polymers (Aghabozorg et al, 2007;Chu et al, 2001;Liu & Ding, 2007;Wu et al, 2006). Here, the title complex, {[Cu 2 (idz) 4 (btc)(H 2 O) 2 ] .…”
Section: Tablementioning
confidence: 99%
“…For general background, see: Rao et al (2000). For related structures, see: Aghabozorg et al (2007); Chu et al (2001); Liu & Ding (2007); Wu et al, (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…The recent interest in the crystal engineering of special geometrical and topological coordination polymers arises from their potential application in catalysis, chemical absorption, magnetism and electrical conductivity (For related structures, see: Rao et al, 2000). The benzene-1,2,4,5-teracarboxylate ligand (bta) as a multi-connecting ligand is also an excellent candidate for the structuring of coordination polymers, and comparatively few examples have been reported to date in relation to applying it to the building of coordination polymers (For details of the preparation of related compounds, see: Aghabozorg et al, 2007;Chu et al, 2001;Liu & Ding, 2007;Wu et al, 2006). We report here the synthesis and crystal structure of the title complex, (I) ( Fig.…”
Section: S1 Commentmentioning
confidence: 99%